The Relationship Between Teacher-Student Relationship and School Adjustment in Cilandak South Jakarta - Sugeng Soebardjo, Delia Ananda; Fidrayani (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
The relationship between teachers and children plays an important role in determining children's adjustment to school, especially in early childhood education environments. A positive relationship between teachers and children is believed to help children overcome challenges in the adaptation process, thus contributing to their success in the school environment. The purpose of this study was to investigate the relationship between teachers and students with school adjustment in Kindergarten A students. Using a quantitative methodology, this study gathered data from 70 respondents who filled out questionnaires. With a correlation value of 0.604, the study discovered a positive and significant link between school adjustment and the relationship between teachers and students. According to this study, students' school adjustment is positively correlated with the strength of their interaction with their teachers. Furthermore, teacher-student relationships contribute 36.5% to school adjustment, while the remaining 63.5% is influenced by other factors such as family support, social environment, and individual student characteristics. This study emphasizes the importance of teachers' roles in fostering positive relationships with students to support optimal school adjustment processes.